Measles Vaccination Status is Not Related To Serology Laboratory IgM Measles in Cirebon Regency (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
The incidence rate of measles cases in Indonesia is still high at 3.20/1000 population in 2016 while the national target is 0/1000 population. The purpose of this study was to investigate the relationship between vaccination status and laboratory serology test results of IgM measles. The research design used case control, data obtained from secondary data from C1 sheet 2016 Cirebon regency. Samples in this study were 60 positive IgM cases and 34 negative IgM controls that had met inclusion and exclusion criteria. The research instrument uses a document sheet of secondary data of individual measles cases with documentation techniques in data collection. Data analysis using chi square test. Measles vaccination status was not related to serological laboratory test results of IgM (p value = 0.161, OR = 2.124; 95% CI = 0.849-5.315). There was no association between measles vaccination status and serologic laboratory serology test result.